Six ways to get a grip by calling-out racism and enacting allyship in medical education (Canadian Medical Education Journal, 2021)
Actively addressing racism in our faculties of medicine is needed now, more than ever. One way to do this is through allyship, the practice of unlearning and re-evaluating, in which a person in a position of privilege and power seeks to operate in solidarity with a traditionally marginalized group. In this paper, we provide practical tips on how to practice allyship, giving educators and leaders background understanding and important tools on how to actively promote equity and diversity. We also share tips on how to promote inclusivity to more accurately reflect the communities we serve. Through six broad actions of being, knowing, feeling, doing, promoting, and acting, we can empower individuals to become allies and address racism in medical education and beyond. Creating psychologically safe spaces, educating ourselves on our complex histories and how they influence the present, recognizing racism, and advocating for change, augments awareness from which we can pivot conversations. Acknowledging potential feelings of shame, guilt, and embracing our loss of privilege, allow necessary, but challenging, personal growth to occur. Finally, dismantling the racist structures that exist within medicine, moving us beyond individual interventions, will address the systemic nature of racism in medicine. Everyone can find a starting place within this guide, as simple, consistent actions foster change in our spheres of influence; and the ripple effect of these changes will impact attitudes and behaviours broadly.